Effect of citral partitioning on structural and mechanical properties of lipid membranes - Saraf, Deepashri; Porte, Sudha; Sengupta, Durba (European Physical Journal-Special Topics, 2024)
Delineating the interactions of cellular metabolites with lipid membranes and their effects on membrane physical and mechanical properties constitutes a key step for comprehensively understanding their biological function. The plant metabolite-citral is widely used in biotechnological and cosmeceutical processes, but significant gaps remain in our understanding of how it affects cellular membranes that it interacts with. In this study, we unravel the molecular mechanisms underlying the interactions of citral with compositionally distinct model membranes using atomistic molecular dynamics simulations. Specifically, we investigate two distinct membrane compositions: the neutral phosphatidylcholine-phosphatidylethanolamine (DOPC:DOPE) bilayer, representing mammalian cell membranes and the anionic phosphatidylcholine-phosphatidylglycerol (DOPC:DOPG) bilayer, mimicking bacterial cell membranes. Our simulations reveal that citral molecules readily partition into both membranes without distinct composition-dependent effects. Monomeric citral molecules localize mainly at the interface of the acyl chain region of the lipids, and a few translocation events are sampled in the simulations. Interestingly, we observe small differences in lipid fluidity although the citral molecules significantly influence the rigidity of lipid bilayers, and a higher bending modulus was observed in DOPC:DOPE lipid bilayers compared to DOPC:DOPG bilayers. Further, citral partitioning induces an increased tendency for lipid demixing in DOPC:DOPE membranes, as evidenced by the decreased values of the Shannon entropy. Our work is an important step to elucidate the molecular processes that underlie the differential impact of cell metabolites on compositionally distinct lipid membranes.

Anomalous membrane organization by omega-6 and omega-9 fatty acids - Porte, Sudha; Pandia, Swaratmika; Joardar, Ankita; Saraf, Deepashri; Pinjari, Aadil; Chakraborty, Hirak; Sengupta, Durba (Physical Chemistry Chemical Physics, 2025)
Omega fatty acids are currently being marketed as healthy food supplements as they have been implicated in multiple pathophysiological conditions, such as reducing plaque formation of A beta peptide and inhibiting SARS-CoV-2 infection. Their mode of action has been hypothesized to be via membrane reorganization by the unsaturated acyl chains, leading to the modulation of lipid-protein cross-talk. However, the lack of molecular details led us to evaluate the molecular effect of omega-6 (linolenic acid) and omega-9 (oleic acid) fatty acids on membrane organization using a consolidated approach of fluorescence spectroscopy and all-atom molecular dynamics simulation. Our results show that the effect of these omega fatty acids is sensitive to their protonation states. Contrary to the accepted notion that chain unsaturation causes membrane disordering, both experimental and simulation results demonstrate that protonated linoleic acid promotes membrane ordering, despite having two unsaturations at the fatty acyl chain. However, protonated oleic fatty acid, with reduced unsaturation, disordered the acyl chain area of the lipid membranes. Equally surprisingly, deprotonated oleic acid orders, whereas deprotonated linoleic acid disorders, the membrane core region. Interestingly, while the lipid order parameter measurements from simulations did not capture these subtle differences, the calculated rotational autocorrelation function of a membrane dye was in line with experimentally measured apparent rotational correlation times. Our work provides a comprehensive revised molecular picture of the effect of omega fatty acids on membranes and highlights the importance of rigorous comparative approaches, as experimental and simulation studies in isolation can sometimes lead to inconsistent results.

A Molecular View of Lipid Nanoparticles: Insights into their Morphology and Structural Plasticity - Porte, Sudha; Vadhana, V.; Sengupta, Durba (Small, 2025)
Lipid nanoparticles (LNPs) have emerged as versatile delivery vehicles for nucleic acid-based therapeutics. Despite their increasing importance, the molecular structure and physico-chemical characteristics of LNPs still remain unclear. In this review, the structural features and phase behavior of LNPs are highlighted. First, the various compositional elements, such as cationic lipids, helper lipids and sterols are discussed, illustrating their functional roles in the self-assembly and stability of LNPs. Molecular models derived from experimental and computational approaches are discussed to provide insights into the structural organization of the LNP components. The influence of sterols and helper lipids in modulating LNP architectures, including membrane fluidity and phase separation, which are key factors for both fusion potential and endosomal escape, is discussed. Variations in sterol content and headgroup chemistry can induce transitions from lamellar to non-lamellar structures, thereby influencing gene transfection outcomes. Further, how cationic lipids induce structural phase transitions, such as lamellar-to-hexagonal and inverse cubic rearrangements under physiological and acidic pH, mimicking extracellular and endosomal conditions, are described. These transitions play a pivotal role in ribonucleic acid (RNA) release and membrane fusion events. This comprehensive review allows to reconcile molecular and structural dynamics that would be necessary for rational design of RNA delivery systems.
Keywords: drug delivery; lipid nanoparticles; phase separation; vaccine delivery